Research on the Spatial Location Design of Guidance Signage Systems to Connect the Space of Transit-Orientated Development Sites Based on Multi-Software Analysis - Xue Ma; Qingjuan Yang (Buildings)
In the context of intensive urban development strategies, the Transit-Oriented Development (TOD) model has emerged as a crucial strategy, requiring a high degree of integration of various functional spaces and traffic flows in transport stations. Complex spaces and traffic flows require an effective Guidance Signage System design to ensure efficient guidance and easy transfers. In order to choose the spatial location of the Guidance Signage System in the connecting space of TOD stations and to improve the efficiency of their guidance and visual saliency, three types of connecting space, namely, channel bifurcation nodes, atrium threshold zones, and sunken plaza interface areas were selected. In total, 18 signage system setup areas were derived from the overlapping visual domains of signage and human visual domains using the Depthmap10 and Massmotion11.5 software (six areas in each type of articulation space), which were then combined with eye-tracking technology to analyze the visual saliency of the signage system’s layout position on the passengers. The experiments show that the signage location affects passengers’ visual attention to a certain extent, and there are differences in the location of high display degrees in different connecting spaces, which require differentiated layouts. This paper summarizes the best spatial location design strategy for the Guidance Signage System according to different connecting spaces, providing more scientific guidance for the spatial location design of the Guidance Signage System for sites connecting spaces. This is essential for enhancing user navigation efficiency, minimizing confusion, and improving overall spatial usability in complex environments.